Performance of Wheat Genotypes under Irrigated Conditions in Far Western Terai of Nepal (KMC Journal, 2024)
Wheat, the most important food crop in terms of food and nutrition security in Nepal, production could not meet the demand of growing population due to limited use of high yielding variety and use of inappropriate variety in the context of increasing heat stress during ripening. For assessing the performance of different wheat genotypes, this study was carried out during November 2022 to April 2023 at Agronomy Farm of Far Western University, Kailali, Nepal. The study was designed in Randomized complete block design (RCBD) with three replications. Eleven genotypes with nine Nepal lines and two Bhairhawa lines were evaluated and compared with a popular variety, Vijay for their performance at Tikapur condition. The result revealed the highest grain yield from NL 1506, recording 3.36 t/ha, which was statistically at par with NL 1452, NL 1488 and BL 5116 at 5% level of significance. The popular variety Vijay yielded only 3.02 t/ha which was statistically at par with NL 1638, but was inferior to NL 1450. Statistically poor performance was observed in the genotypes NL 1445 and BL 4984.